Neuroimaging features of WOREE syndrome: a mini-review of the literature - Laura Battaglia; Giovanna Scorrano; Rossana Spiaggia; Antonio Basile; Stefano Palmucci; Pietro Valerio Foti; Corrado Spatola; Michele Iacomino; Franco Marinangeli; Elisa Francia; Francesco Comisi; Antonio Corsello; et al. (Frontiers Media S.A., 2023)
The WWOX gene encodes a 414-amino-acid protein composed of two N-terminal WW domains and a C-terminal short-chain dehydrogenase/reductase (SDR) domain. WWOX protein is highly conserved among species and mainly expressed in the cerebellum, cerebral cortex, brain stem, thyroid, hypophysis, and reproductive organs. It plays a crucial role in the biology of the central nervous system, and it is involved in neuronal development, migration, and proliferation. Biallelic pathogenic variants in WWOX have been associated with an early infantile epileptic encephalopathy known as WOREE syndrome. Both missense and null variants have been described in affected patients, leading to a reduction in protein function and stability. The most severe WOREE phenotypes have been related to biallelic null/null variants, associated with the complete loss of function of the protein. All affected patients showed brain anomalies on magnetic resonance imaging (MRI), suggesting the pivotal role of WWOX protein in brain homeostasis and developmental processes. We provided a literature review, exploring both the clinical and radiological spectrum related to WWOX pathogenic variants, described to date. We focused on neuroradiological findings to better delineate the WOREE phenotype with diagnostic and prognostic implications.